Grain Sorghum Cost-Return Budget in Southeast Kansas - Fogleman, Sarah L.; Kilgore, Gary L. (My University, 2001)
This publication outlines the expected costs and returns for grain sorghum production in southeast Kansas.
MF995_2001_10
Keywords: MF995; Economics; Crops; MF